PROMOTING LIVE WORKSHEETS TO RAISE SENIOR HIGH STUDENTS’ SPEAKING CONFIDENCE AND MOTIVATION - Teresa, Amelia; Febria, Desty (Department of English Education, Universitas Panca Sakti Bekasi, 2023)
Based on observations made in one of many existing senior high specialized government schools specifically in SMAN 20 Batam where English is a compulsory subject, the writer found that speaking motivation and confidence is still lacking, as well as a lack of technology exploration. By combining technology and face-to-face instruction, the method of blended learning (BL) used in this study utilizes Classroom Action Research (CAR) method. In addition to the pre-test and scoring rubric of the CAR cycle, Live Worksheet is provided as a breakthrough to solve the shortcoming by executing the online interactive platform as a post-test (final evaluation). As a result, of the Live Worksheet implementation of the blended learning CAR method, 90% of students of a representative 10th senior grade class have increased their speaking motivation and confidence, with 3 out of 5 speaking skill elements such as grammar structures, fluency, and pronunciation showing improvement skyrocketed to 80 points, contrast to the low pre-test result of 60 points for each element.